ANALISIS EFEKTIVITAS PERENCANAAN PAJAK PADA PERHITUNGAN PAJAK PENGHASILAN BADAN PT. EMPAT SEKAWAN LOGISTICS TAHUN 2023 - Harjo, Dwikora; Iskandar, Taslim (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
PT Empat Sekawan Logistics is suspected of being less efficient in managing tax savings because it relies entirely on freelance services for fiscal and tax reporting, especially in fiscal corrections and income tax calculations. This study examines the effectiveness of tax planning at PT Empat Sekawan Logistics in calculating Corporate Income Tax, addressing inefficiencies due to reliance on freelance services for fiscal reporting. Using a descriptive quantitative method, the research evaluates the company’s tax planning effectiveness, identifies obstacles such as differing interpretations of tax regulations, and reviews measures to address these challenges. Findings reveal that the company saved IDR 39,931,811 in taxes in 2023 through effective tax planning. To overcome obstacles, tax officers engage in discussions with authorities to align perceptions before implementing tax strategies.